ANALISIS KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII. 7 SMPN 9 PADANG - Viktor; Mulia Suryani; Audra Pramitha Muslim (Matedukasia, 2023)
This research is Motivated by the low ability of students to understand mathematical concepts. The purpose of this study was to determine how the methematical ability of class VIII.7 students of SMP Negeri 9 Padang. The research method used is descriptive with a quantitative approach. Sampling technique using purposive sampling. The instrument used to collect data is in the form of a concept understanding ability test and interviews. Test results are analyzed based on indicators of concept understanding. The results of this study indicate that students’ ability to understand Mathematical concepts is high on indicators of restating a concept, developing necessary and sufficient conditions for a consept and clarifyng  objects according to certain properties (according to the concept). And is classified as being in the indicator of presenting concsps in the from of mathmatical representations and applying concepts or problem solving algorithms.